Neurotized sural flap: An alternative in sensory reconstruction of the foot and ankle defects. Issue 3 (8th September 2014) - Tan, Onder; Aydin, Osman E.; Demir, Recep; Barin, Ensar Z.; Cinal, Hakan; Algan, Said
Abstract : Introduction: The sensory reconstruction of the lower extremity is one of the main goals in lower extremity reconstruction. Reconstructive options endowing sensory recovery are limited. The aim of this report is to evaluate the neurotized sural flap in reconstruction of foot and ankle defects. Patients and Methods: Seven cases that were operated for foot and ankle skin defects with the neurotized sural flap were reported. The largest flap was 10 cm × 14 cm in size. Median age was 38 years. Four defects were on the heel, two were on the ankle, and one was on the dorsum of the foot. The sural nerve was coaptated to a recipient nerve in seven patients. Results: All flaps survived totally. Follow‐up time ranged between 9 and 29 months. All cases had hot–cold perception and two‐point discrimination at average 14 ± 1.63 mm at 6th month. Sensory conduction test revealed very low action potentials related to stimulation of the flap. Conclusion: The neurotized sural flap is a versatile modification, for the sensory reconstruction of the moderate size foot and ankle defects. © 2014 Wiley Periodicals, Inc. Microsurgery 35:183–189, 2015.